Using bimetallic electrode coaxial accelerator for batch superhard material Tin-Сu; International Congress on Energy Fluxes and Radiation Effects (EFRE-2014) - Sivkov A. A. Aleksandr Anatolyevich; Usikov A. I.; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich (2014, 2014)
Title screen